FACTORS AND WAYS TO INCREASE INVESTMENT ACTIVITY IN THE STOCK MARKET - Kamilova Sevara Anvarovna (Web of Journals Publishing, 2024)
The stock market plays a key role in the economy, being one of the main tools for attracting investments and financing companies. Investment activity in the stock market has a significant impact on the financial stability and growth of the country's economy as a whole. In this article, we will look at the factors influencing investment activity in the stock market, as well as ways to increase it.
Keywords: factors, ways, increase, investment activity, stock market, economic stability, regulation, legal protection, macroeconomic indicators.